Порівняльна характеристика впливу різних методів контрацепції на якість життя жінки - Горбунова, О. В.; Новосад, А. В. (Clinical Endocrinology and Endocrine Surgery, 2010)
Usage of transdermal hormonal system by women of reproductive age is effective and safe. It is approved by restoration of period's rhythm, low frequency of side effects, subjective improvement of life quality.